A Quantitative Description of the Henan Famine of 1942 - Garnaut, A (2013)
The Henan famine of 1942 occurred during the middle of the Sino-Japanese war, in a province that was divided between Japanese, Nationalist and Communist political control. Partly due to this wartime context, existing accounts of the famine rely almost exclusively on eyewitness reports. This paper presents a range of statistical sources on the famine, including weather records, contemporary economic surveys and population censuses. These statistical sources allow similarities to be drawn between the Henan famine and other famines that occurred during the Second World War, such as in Bengal, when the combination of bad weather, war-induced disruptions to food markets, and the relegation of famine relief to the war effort, brought great hardship to civilians living near the war front. Copyright © Cambridge University Press 2013.